Participation of Rural Women in Livestock Management Activities in Cooch Behar District of West Bengal - Bose, Dipak Kumar; Srivastava, J.P.; Masih, Edward; Bose, Hira (Indian Journal of Extension Education, 2013)
A study was carried out to ascertain the participation of rural women in livestock management, using a pretested  structured interview schedule for collecting the relevant information. One hundred and twenty rural women randomly  were selected from purposively selected one block and four villages selected randomly. The study revealed that majority  of the respondents were of middle aged, illiterate and marginal farmers having low annual income. They belonged to joint  family and had agriculture as the main occupation. It was found that majority of the respondents had high level of  participation in various activities of livestock management. Age, land holding and livestock possession were found to be  positively and significantly correlated with livestock management practices.
Keywords: Socio-personal; participation; rural women; livestock management